ANALISIS SISTEM AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN MANAJERIAL PADA BANK BTN CABANG PANAKKUKANG - Rendi Morhum; Ismail Badollahi; Nurhidayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
RENDI MORHUM. 2025. Analysis of Management Accounting System inManagerial Decision-Making at Bank BTN Panakkukang Branch.Undergraduate Thesis. Department of Accounting, Faculty of Economics andBusiness, Universitas Muhammadiyah Makassar. Supervised by: IsmaiBadollahi and Nurhidayah.This study aims to analyze the role of the management accounting system inmanagerial decision-making at Bank BTN Panakkukang Branch. The researchmethod employed is descriptive qualitative through interviews, observation, anddocumentation. The findings indicate that the management accounting systemprovides relevant, accurate, and timely information that greatly assists managersin the processes of planning, controlling, and performance evaluation. Suchinformation also supports the accuracy of strategies and policies determined bythe branch leadership. Thus, the management accounting system makes asignificant contribution to enhancing the effectiveness and quality of managerialdecision-making in the banking sector.